Evaluating the explanatory value of Brahimi And Ahmed’s Seven Deadly Sins Of Mediation : the case of the Malagasy mediation of 2009-2014 - Schoeman, Maxi (University of Pretoria, 2019)
Dissertation (MA Security Studies)--University of Pretoria 2019.